2002
DOI: 10.1046/j.0909-752x.2001.10312.x
|View full text |Cite
|
Sign up to set email alerts
|

Hydration vs. skin permeability to nicotinates in man

Abstract: Background/aims: Prolonged skin occlusion increases stratum corneum water content and often increases skin permeability and irritant dermatitis. As skin wetness from wearing diapers is considered an important factor favouring the onset of diaper dermatitis, optimal diapering might decrease skin hyperhydration and dermatitis. Our aim is to define the quantitative relationship between nicotinate ester (a model penetrant) skin permeability and hydration, as measured by water evaporation rate (WER), decay curves (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
1
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 23 publications
0
20
1
3
Order By: Relevance
“…Thus, increased permeation of hydrophilic methyl nicotinate (log Kow 0.7) as well as of lipophilic hexyl nicotinate (log Kow 3.1) was demonstrated through hydrated human skin even after 10 min of exposure to water (Zhai et al 2002). Bucks et al (1999) showed that occlusion enhanced the penetration of the more lipophilic steroids progesterone (log Kow 3.9), testosterone (log Kow 3.3) and estradiol (log Kow 2.5) but did not change the penetration of the more hydrophilic hydrocortisone (log Kow 1.6).…”
Section: Skin Hydrationmentioning
confidence: 92%
“…Thus, increased permeation of hydrophilic methyl nicotinate (log Kow 0.7) as well as of lipophilic hexyl nicotinate (log Kow 3.1) was demonstrated through hydrated human skin even after 10 min of exposure to water (Zhai et al 2002). Bucks et al (1999) showed that occlusion enhanced the penetration of the more lipophilic steroids progesterone (log Kow 3.9), testosterone (log Kow 3.3) and estradiol (log Kow 2.5) but did not change the penetration of the more hydrophilic hydrocortisone (log Kow 1.6).…”
Section: Skin Hydrationmentioning
confidence: 92%
“…Test sites were covered with wet occlusive patches for 10 minutes to 3 hours. Capacitance increased with the increased use of the occlusive patches, but skin impregnation with nicotinates was not correlated with exposure time or skin hydration . These reports showed that occlusion induces skin hydration and increases permeability in vivo.…”
Section: Introductionmentioning
confidence: 88%
“…We evaluated MN permeability with the procedures used in previous studies . Briefly, filter papers that were 5 mm in diameter and contained 5 μL of 0.007% (wt/wt) MN aqueous solution were applied to the test areas for 15 seconds.…”
Section: Methodsmentioning
confidence: 99%
“…Skin hydration is known to enhance permeant diffusivity through the membrane [62]. Occlusion of skin is associated with corneocyte swelling and an increase in the water content of the intercellular lipid domain [63,64].…”
Section: Impact Of Occlusionmentioning
confidence: 99%